2022
DOI: 10.1126/sciimmunol.abm7200
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized thioredoxin-1 restrains the NLRP1 inflammasome

Abstract: The danger signals that activate the NLRP1 inflammasome have not been established. Here, we report that the oxidized, but not the reduced, form of thioredoxin-1 (TRX1) binds to NLRP1. We found that oxidized TRX1 associates with the NACHT-LRR region of NLRP1 in an ATP-dependent process, forming a stable complex that restrains inflammasome activation. Consistent with these findings, patient-derived and ATPase-inactivating mutations in the NACHT-LRR region that cause hyperactive inflammasome formation interfere w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 56 publications
2
27
0
Order By: Relevance
“… 21 , 28 MeBs, which synergizes with VbP to induce more pyroptosis in these cell lines, was used as a positive control in this experiment. 8 , 26 Consistent with our previous results, 27 we found that dithiothreitol (DTT), N-acetyl cysteine (NAC), reduced L-glutathione (GSH), and trolox did not synergize with VbP to induce more NLRP1 or CARD8 activation in this assay ( Figures 1A , 1B , and S2A ). Intriguingly, we observed that ferrostatin-1 (Fer-1), a lipophilic antioxidant that blocks an iron-dependent form of cell death called ferroptosis, 29 unlike other commonly used antioxidants, appeared to slightly synergize with VbP in RAW 264.7 and MV4;11 cells at a high (40 μM) concentration ( Figures 1A , 1B , and S2A ).…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“… 21 , 28 MeBs, which synergizes with VbP to induce more pyroptosis in these cell lines, was used as a positive control in this experiment. 8 , 26 Consistent with our previous results, 27 we found that dithiothreitol (DTT), N-acetyl cysteine (NAC), reduced L-glutathione (GSH), and trolox did not synergize with VbP to induce more NLRP1 or CARD8 activation in this assay ( Figures 1A , 1B , and S2A ). Intriguingly, we observed that ferrostatin-1 (Fer-1), a lipophilic antioxidant that blocks an iron-dependent form of cell death called ferroptosis, 29 unlike other commonly used antioxidants, appeared to slightly synergize with VbP in RAW 264.7 and MV4;11 cells at a high (40 μM) concentration ( Figures 1A , 1B , and S2A ).…”
Section: Resultssupporting
confidence: 91%
“…Indeed, oxidative power is critical for protein folding in the ER 44 ; it seems possible that oxidative power plays a similar, but as-yet-unknown, role in the folding of cytosolic proteins, including NLRP1’s and CARD8’s NT fragments. In addition, we recently discovered that oxidized TRX1 stabilizes NLRP1 NT’s structure, 27 which we now speculate serves as a “checkpoint” to ensure misfolding is indeed associated with reductive stress. Whether a redox-sensitive protein similarly regulates the folding of the CARD8 NT remains to be determined.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations